2016
DOI: 10.1186/s12864-016-2808-x
|View full text |Cite
|
Sign up to set email alerts
|

Genomic analysis of nontypeable pneumococci causing invasive pneumococcal disease in South Africa, 2003–2013

Abstract: BackgroundThe capsular polysaccharide is the principal virulence factor of Streptococcus pneumoniae and a target for current pneumococcal vaccines. However, some pathogenic pneumococci are serologically nontypeable [nontypeable pneumococci (NTPn)]. Due to their relative rarity, NTPn are poorly characterized, and, as such, limited data exist which describe these organisms. We aimed to describe disease and genotypically characterize NTPn causing invasive pneumococcal disease in South Africa.ResultsIsolates were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
27
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(32 citation statements)
references
References 35 publications
4
27
0
Order By: Relevance
“…This suggests non-typeable S. pneumoniae are not simply bacteria that have lost their capsule, but have also undergone other adaptive changes in specialising to a distinct niche. This may account for the distinct pathogenesis of unencapsulated strains, which do not cause severe invasive disease ( 30 ), but are known to cause outbreaks of conjunctivitis ( 31 ).…”
Section: Resultsmentioning
confidence: 99%
“…This suggests non-typeable S. pneumoniae are not simply bacteria that have lost their capsule, but have also undergone other adaptive changes in specialising to a distinct niche. This may account for the distinct pathogenesis of unencapsulated strains, which do not cause severe invasive disease ( 30 ), but are known to cause outbreaks of conjunctivitis ( 31 ).…”
Section: Resultsmentioning
confidence: 99%
“…This may be because their role in disease has been limited. For example, in South Africa over a 10-year period spanning from before to after PCV, and in the United States over a 3-year period in the post-PCV era, nontypeables rarely caused disease [44, 45]. We nonetheless advocate for the inclusion of nontypeable strains in epidemiological surveillance studies owing to their increasing importance and potential for maintaining transmission.…”
Section: Discussionmentioning
confidence: 99%
“…PspK has been described as an adhesin that allows NESp to colonize as efficiently as encapsulated pneumococci ( 14 , 15 ). Remarkably, extensive surveillance of invasive pneumococcal disease (IPD) isolates has revealed an association of invasive disease with NESp expressing oligopeptide binding proteins AliC and AliD despite the absence of a protective, antiphagocytic capsule thought to be necessary to establish IPD ( 12 , 16 20 ). A survey of pneumococcal isolates in Switzerland from 1998 to 2002 first exposed the isolation of NESp expressing AliC and AliD from a blood sample ( 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…Surveillance of IPD isolates in the United States from 2006 to 2009 identified that 67% of pneumococcal isolates lacking cps genes encoded both aliC and aliD in their cps locus ( 19 ). In a surveillance study spanning 2003 to 2013 in South Africa, 82% of NESp IPD isolates with complete deletion of cps genes were described as containing aliC and aliD in place of their cps genes ( 20 ). Collectively, the isolation of IPD-associated NESp expressing AliC and AliD from geographically distinct areas of isolation suggests that these oligopeptide binding proteins afford a selective advantage during invasive disease.…”
Section: Introductionmentioning
confidence: 99%